2013
DOI: 10.1007/s00508-013-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

COPD: an underdiagnosed disease at hospital environment

Abstract: Our study showed that spirometric screening together with the CAT questionnaire may improve the awareness of disease and may determine undiagnosed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…These studies have found between 25 and 34% of the study populations to have undiagnosed COPD. [9,16] This is not consistent with the findings of this study where a considerably smaller proportion the examined patients were diagnosed with COPD. There are several possible explanations of this.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…These studies have found between 25 and 34% of the study populations to have undiagnosed COPD. [9,16] This is not consistent with the findings of this study where a considerably smaller proportion the examined patients were diagnosed with COPD. There are several possible explanations of this.…”
Section: Discussioncontrasting
confidence: 89%
“…There are several possible explanations of this. In the study by Kart et al [16] examining outpatients and patients hospitalized for elective treatment, a considerably larger proportion of the study population were able to participate in spirometry; in the study by Nielsen et al [9] all inpatients were examined, and in neither of these studies the study populations were followed up in stable state. In fact, in this study a larger proportion of the study population had airflow obstruction at the initial examination than in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Even when it is there, professionals in LMIC are often not being trained properly on how to use spirometers or interpret spirometry results. There is concern that COPD burden has been underestimated, owing to over-reliance on doctor' s diagnosis, with many diagnoses not being based on spirometry and international diagnostic guidelines [20]. The lack of routine COPD data collation and effective health information management system in many LMIC also implies that these settings could have been grossly underrepresented in global burden of COPD estimates [11].…”
mentioning
confidence: 99%
“…COPD was diagnosed using a spirometry reference test rather than the mini-spirometry employed in most similar studies. 14,15 No COPD-asthma overlap was to be feared because asthma cases had no evidence of obstructive spirometry. Finally, we used a sound statistical methodology based on bootstrap resampling to select the best subset of independent covariates and to adjust for overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The COPD Assessment Test (CAT) was initially developed and validated for routinely assessing and monitoring COPD patients. 12,13 It was later used to help screen for COPD in both smokers, 14,15 and the general population. 16,17 Subjects who the CAT questionnaire indicated were at risk then underwent diagnostic spirometry and appropriate medical management, if necessary, before any severe symptoms developed.…”
Section: Introductionmentioning
confidence: 99%